The singular purification of Jose Maria de Zuaznávar as counselor of Navarre in 1823 - González Fuertes, Manuel Amador (Huarte de San Juan. Geografía e Historia, 2017)
Within a set of records purification of numerous magistrates preserved in the AHN scarcely used by researchers, the file purification José María Zuaznávar presents a series of singularities that are explored in this article. The article discusses the historiographical oblivion of Zuaznávar, the peculiarities of the file that contravene the rules of the Regency to process purifications and uniqueness of the text itself, an absolutist argument as a basis for the preface to the second edition of his Ensayo histórico-crítico sobre la legislación de Navarra.
Keywords: Purification; absolutism; anti-foralism; magistracy